Estimation of SAW velocity and coupling coefficient in multilayered piezo-substrates AlN/SiO2/Si - Malik, A.F. (Institute of Electrical and Electronics Engineers Inc., 2017)
In this study, the problem of estimating surface acoustic wave (SAW) velocity and coupling coefficient for multi-layered piezo-substrates is investigated in Aluminum Nitride/Silicon Dioxide/Silicon (AlN/SiO2/Si) using energy dissipation method. Assuming SAW energy lying within 10 times of wavelength (λ0) from the surface with ∼ 90 energy lying within 1 λ0, layers of different materials can cause a significant variations in SAW velocity. The assumption stated above, herein called as Energy Method, is employed to estimate SAW velocity in layered piezo-substrates. SAW device is fabricated using conventional lithography process and AlN is deposited using non-conformal physical vapor deposition (PVD) technique. The transfer characteristics of the SAW device are then measured using vector network analyzer (VNA) and thus operating central frequency fo is obtained to use in computation of SAW velocity. Based on the results, it is observed that energy method is a suitable choice to estimate SAW velocity with an average error of ∼ 1.6 . Further, piezoelectric coupling coefficient is also estimated using measured S-parameters for various SAW devices and found close to literature based values. © 2016 IEEE.